2019
DOI: 10.1111/1753-0407.12900
|View full text |Cite
|
Sign up to set email alerts
|

Associations between metformin use and vitamin B12 levels, anemia, and neuropathy in patients with diabetes: a meta‐analysis

Abstract: Highlights• This meta-analysis found that metformin use was associated with a significantly increased risk of vitamin B 12 deficiency and significantly lower serum vitamin B 12 concentrations in a dose-and duration-dependent manner in patients with diabetes. • The meta-analysis did not find significant associations between metformin use and the risk of anemia or neuropathy in patients with diabetes. • Annual vitamin B 12 assessment in diabetic patients taking metformin is recommended, and appropriate preventat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
94
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 48 publications
7
94
1
10
Order By: Relevance
“…While most studies, including meta-analysis reviews, agree that there is an association between vitamin B12 deficiency and the intake of metformin in T2DM patients, a small number of studies have disputed this relationship. 4,5,15,16 The current study confirmed the association between a high metformin dose and vitamin B12 deficiency as concluded by previous studies. 3,10 Patients were found to be at a higher risk of developing vitamin B12 deficiency if they took a larger dose of metformin (>2000 mg/day) and for a longer duration (>4 years).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While most studies, including meta-analysis reviews, agree that there is an association between vitamin B12 deficiency and the intake of metformin in T2DM patients, a small number of studies have disputed this relationship. 4,5,15,16 The current study confirmed the association between a high metformin dose and vitamin B12 deficiency as concluded by previous studies. 3,10 Patients were found to be at a higher risk of developing vitamin B12 deficiency if they took a larger dose of metformin (>2000 mg/day) and for a longer duration (>4 years).…”
Section: Discussionsupporting
confidence: 91%
“…2 A significant decrease in the levels of serum vitamin B12 were observed in studies of patients with type 2 DM (T2DM) who were taking metformin compared to those who were not, and in studies comparing patients with T2DM taking metformin and those without T2DM. [3][4][5][6][7][8] A randomised controlled trial conducted over 4.3 years reported a significant decrease in serum vitamin B12 concentration after metformin treatment. 9 Patients were found to be at a higher risk of developing vitamin B12 deficiency if they took larger doses of metformin and for a longer duration.…”
mentioning
confidence: 99%
“…The BARI 2D study showed that insulin‐sensitizing therapy (metformin and/or thiazolidinediones), as opposed to insulin‐providing therapy (sulfonylureas/meglitinides, with or without insulin), reduced the 4‐year cumulative incidence of DPN in people without DPN at baseline, but had no impact on people with established DPN. Concern has been raised regarding metformin‐associated vitamin B 12 deficiency and peripheral neuropathy; however, a recent meta‐analysis has shown that, whilst long‐term metformin use is associated with vitamin B 12 deficiency, it is not related to an increased prevalence of DPN . Furthermore, we have recently shown that the prevalence and severity of DPN and painful DPN were similar in people with and without B 12 deficiency .…”
Section: Treatment Of Diabetic Peripheral Neuropathymentioning
confidence: 85%
“…Nonetheless, it is worthy of note that we did not observe significant association between the manifestations of neuropathy and anemia with vitamin B 12 deficiency. A possible reason for this finding may be due to the direct neuroprotective effect of metformin through its glucose-lowering effect and antihyperglycemic-independent, direct anti-neuropathic impact on neurons including inhibition of oxidative stressrelated apoptotic cell death [36,37]. Studies by Ahmed et al in South Africa and Russo et al in Italy [38,39] also found no significant difference in the presence of neuropathy between subjects with normal vitamin B 12 levels and those with vitamin B 12 deficiency.…”
Section: Discussionmentioning
confidence: 98%